Worldwide research productivity in the field of endocrinology and metabolism--a bibliometric analysis - Zhao, Xiyan; Ye, Ru; Zhao, Linhua; Lin, Yiqun; Huang, Wenjing; He, Xinhui; Lian, Fengmei; Tong, Xiaolin (Endokrynologia Polska, 2015)
Recently, significant contributions to the study of endocrinology and metabolism have been made. The national contribution, however, has not been reported. The aim of this study was to assess national efforts in the field of endocrinology and metabolism. A Web of Science search was performed using subject categories "endocrinology & metabolism" to identify articles published from 2010 to 2014. The total and per capita numbers of articles and citations were analysed for different countries. A total of 79,394 articles were published on endocrinology and metabolism from 2010 to 2014. Most were published in North America, East Asia, and Europe. The majority (82.28%) were reported by authors in high-income countries, 17.64% were published in middle-income countries, and only 0.08% were published in low-income countries. Authors in the United States published the most articles (27.38%), followed by China (7.22%), Italy (5.70%), the United Kingdom (5.6%), and Japan (5.54%). Articles published by authors in the United States had the most citations (260,934). A positive correlation was found between the number of publications and population/gross domestic product (GDP; p < 0.01). When normalised to population size, the ranking for the most publications was Denmark, Sweden, and the Netherlands; when normalised to GDP, the ranking was Denmark, Greece, and the Netherlands. The majority of endocrinology and metabolism articles were published by authors from high-income countries with few from low-income countries. The United States was the most productive country. However, when population size and GDP were considered, some European countries were ranked higher.